2009
DOI: 10.1097/tp.0b013e3181a23837
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Chronic Kidney Disease Treatment Targets in Renal Transplant Recipients: Results From a Cross-Sectional Study in Spain

Abstract: CKD and their complications were prevalent in renal transplant recipients. The control of some of these complications is far below targets established for nontransplant CKD patients despite a progressive intensification of therapy as graft function declines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…Most currently available data come from cross-sectional studies that have examined the prevalence of anemia in heterogeneous populations of patients with different years of follow-up (11). The present study has analyzed a broadly representative cohort of patients, which allows to describe accurately the presence and management of anemia and to analyze its relationship with the clinical course over approximately 3 years after transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…Most currently available data come from cross-sectional studies that have examined the prevalence of anemia in heterogeneous populations of patients with different years of follow-up (11). The present study has analyzed a broadly representative cohort of patients, which allows to describe accurately the presence and management of anemia and to analyze its relationship with the clinical course over approximately 3 years after transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to the general and chronic kidney disease (CKD) populations, risk factors for hypertension after transplant include determinants of both donor and recipient origin and also factors that relate to the transplant process and immunosuppression [5]. Despite increased awareness of the adverse effects of arterial hypertension in both graft and patient survival, long-term studies have shown that arterial hypertension in the transplant population has not been controlled adequately [8]. Uncontrolled hypertension is not synonymous with resistant hypertension.…”
Section: Introductionmentioning
confidence: 98%
“…[14] In adult studies only 42–82% of hypertensive patients with CKD were on medical therapy and only 20–60% of patients with CKD or a kidney transplant were treated for uncontrolled cholesterol. [1516] Together with our findings these studies suggest that current systems of chronic disease management do not reliably provide optimal care. In order to improve long-term outcomes, further research should explore system redesign as a means to improve quality of care.…”
Section: Discussionmentioning
confidence: 58%
“…[56] Accordingly, guidelines published as early as 2003 recommend screening for, and strict control of modifiable CVRFs in these patients. [513] Recent publications have highlighted the suboptimal quality of care for children with chronic illnesses in the primary care setting,[14] and for adults with CKD[15] or a kidney transplant (TXP),[16] yet little is known regarding the patterns of care for adolescents with kidney disease in relation to published guidelines.…”
Section: Introductionmentioning
confidence: 99%